SELF-ASSESSMENT AMONG THE STUDENTS OF INTERNATIONAL BUSINESS ADMINISTRATION SAM RATULANGI UNIVERSITY ON THE ENTREPRENEURIAL POTENTIAL - Rumagit, Marimar E.; Massie, James D.D; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The students of IBA are educated and facilitated to become entrepreneurs through various academic programs such as introductory courses and student affair programs such as entrepreneurship courses and entrepreneurial competitions. However, there’s no evaluation that the education and facilitation provided by IBA program is effective enough to create high quality entrepreneur. Therefore, the purpose of this research is to evaluate the entrepreneurial potential by identify and examine the attributes, mindset, and willingness to be self-employed whether the primary objective is to deliver social value or to create economic value. In accordance with this purpose, the self-assessment questionnaire was administered to 50 respondents among the students of International Business Administration, Sam Ratulangi University. As statistical analysis, this research provides Descriptive Statistics and Kruskal Wallis analysis were used. The result revealed that most of IBA students indicate high level of self-evaluation as entrepreneurial attributes but they are not having enough mindset as well as an entrepreneur. However most of them are willing to be entrepreneur with the primary objective is to create economic value. Therefore, IBA program needs to arrange the strategy in order to set a mindset as well as an entrepreneur and increase the preference of delivering social value.Keywords: Entrepreneurship, Entrepreneurial Potential, Self-Assessment